Discursive Marketisation Through Positive Evaluation: A Diachronic Analysis of About Us Texts of Top-Tier Chinese Universities Over the Past Two Decades - Xu, Lihua; Xie, Chaoqun; Lei, Jun (Frontiers in Psychology, 2021)
This study explored the marketisation process of top-tier Chinese universities by scrutinising their self-promotional strategies over the past two decades. Drawing on Martin and White’s (2005) Appraisal framework, we identified all attitudinal markers in the About Us texts posted by 35 top-tier Chinese universities on their official websites at two time-points: the turn of the century and the year of 2021. The 35 universities were drawn from China’s “Double First Class” Initiative that prioritises the development of a select group of elite universities in China. Close textual analyses focussing on the attitudinal markers with reference to their contexts were conducted to identify the themes evaluated in the About Us texts; Wilcoxon signed-rank tests were run to quantitatively compare the relative frequencies of the attitudinal markers between the two phases, which was then supplemented by diachronic qualitative comparisons on the fine-grained linguistic features surrounding the markers. The study identified seven major themes positively appraised by the universities at both time-points. It also revealed diachronic differences in the use of attitudinal markers, reflecting a mediated change of promotional strategies over the past 20 years or so in the Chinese higher education context. These findings point to the influence of market, government, and tradition on Chinese top-tier universities’ promoting strategies and the role of social cognition in shaping student choice. They also suggest the emergence of a higher education system with Chinese characteristics that features a reconciliation of market and government forces.